Indonesia's Global Halal Hub: Competitive Strategies for Leadership - Akim, Akim; Sari, Viani Puspita; Konety, Neneng; Nidatya, Nurfarah (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
Indonesia, with the world's largest Muslim demographic bonus, does not seem to have achieved enough capital to reach the top rank of the global Islamic economy. Although the vision of Global Halal Hub 2024 is supported by the government, this research highlights Indonesia's lack of awareness of its competitive advantages, which attracted the author's attention to explore further. Qualitative and descriptive analysis are the methods in this research. This paper refers to the concepts of Competitive Advantage of Nations developed by Michael E. Porter, namely factor conditions, demand conditions, related and supporting industries, and firm strategy, structure, and rivalry. Through factor condition analysis, it can be seen that to achieve a competitive advantage in the halal industry, Indonesia needs to improve its logistics infrastructure and develop human resource expertise in halal certification, research stimulation, and product innovation. Demand conditions then indicate the need for increased consumer education and diversification of halal products. Meanwhile, the concept of related and supporting industries targets strengthening halal guarantee institutions and government support. The indicators of firm strategy, structure, and rivalry focus on developing global marketing strategies and international partnerships. To achieve Global Halal Hub status, researchers highlight the importance of comprehensive and collaborative approaches, such as integration in strengthening logistics infrastructure, increasing human resource expertise related to halal certification, and increasing research and product innovation. In addition, consumer education and cooperation with institutions and governments play a vital role in creating favorable conditions. Keywords: Comparative Advantage, Halal Hub, Indonesia Indonesia, dengan bonus demografi umat Muslim terbesar dunia, tampaknya belum mencapai modal yang cukup untuk mencapai peringkat teratas perekonomian Islam global. Kendati visi Global Halal Hub 2024 didukung oleh pemerintah, penelitian ini menyoroti masih kurangnya kesadaran Indonesia terhadap keunggulan-keunggulan kompetitif yang dimiliki, sehingga menarik perhatian penulis untuk menelaah lebih lanjut. Metode kualitatif dan analisis deskriptif menjadi metode dalam penelitian ini. Tulisan ini merujuk pada konsep-konsep Competitive Advantage of Nations yang dikembangkan oleh Michael E. Porter, yakni factor condition, demand condition, related and supporting industry serta firm strategy, structure, and rivalry. Melalui analisis factor condition, terlihat bahwa untuk mencapai keunggulan kompetitif dalam industri halal, Indonesia perlu meningkatkan infrastruktur logistik serta pengembangan keahlian sumber daya manusia dalam sertifikasi halal, stimulasi riset, dan inovasi produk. Demand condition kemudian menunjukkan perlunya peningkatan edukasi konsumen dan diversifikasi produk halal. Sementara itu, konsep related and supporting industry menargetkan penguatan lembaga penjaminan halal dan dukungan pemerintah. Adapun indikator firm strategy, structure, and rivalry berfokus pada perlunya pengembangan strategi pemasaran global dan kemitraan internasional. Guna mencapai status Global Halal Hub, peneliti menyoroti pentingnya pendekatan-pendekatan komprehensif dan kolaboratif, seperti integrasi dalam penguatan infrastruktur logistik, peningkatan keahlian sumber daya manusia terkait sertifikasi halal, dan peningkatan riset serta inovasi produk. Selain itu, edukasi konsumen dan kerja sama dengan lembaga serta pemerintah memainkan peran vital dalam menciptakan kondisi yang mendukung. Kata-kata Kunci: Keunggulan Komparatif, Halal Hub, Indonesia